(untitled) (International Journal of Advanced Research in Computer Science, 2017)
Mobile Adhoc Network (MANET) is characterized by mobile hosts, dynamic topology, multi-hop wireless connectivity and infrastructure less ad hoc environment. The adhoc environment is accessible to both legitimate network users and malicious attackers. Moreover, as the wireless links are highly errors prone and can go down frequently due to mobility of nodes, therefore, energy efficient, secure and stable routing over MANET is still a very critical task due to highly dynamic environment. Moreover, the nodes in MANETs are typically powered by batteries which have limited energy reservoir and some times it also becomes very difficult to recharge or replace the battery of the nodes. Hence, power consumption becomes an important issue. The power consumption rate of each node must be evenly distributed to maximize the lifetime of ad hoc mobile networks, and the overall transmission power for each connection request must be minimized. In this paper, we compare a two types of Mobile adhoc network i.e., proactive and reactive for Energy Efficiency in Manet. Energy Efficient is basically termed as which consume a less energy. So, this paper gives comparison about various routing protocols related to Energy Efficiency. Keywords: MANET, PROACTIVE, REACTIVE, Network